Gastrointestinal Stromal Tumor of the Ileum Causing Mechanical Bowel Obstruction: A Case Report - Osman Erdoğan; Zafer Teke; Nihal Aykun; Orçun Yalav (Southern Clinics of Istanbul Eurasia, 2019)
Gastrointestinal stromal tumors (GISTs) are submucosal tumors that stem from regions of the digestive tract, including esophagus, stomach, small intestine, colon and rectum. GISTs most commonly occur in the stomach (50%–60%), the second most commonly in the small intestine (20%–25%), and less frequently in the rectum (5%). They are frequently diagnosed incidentally during radiological studies or endoscopic procedures performed to investigate gastrointestinal tract disease or to surgically treat an emergent condition, such as gastrointestinal hemorrhage, perforation, or obstruction. Surgery is the primary method to confirm the diagnosis of a GIST histopathologically. The primary purpose of surgical treatment in surgically resectable GISTs is to perform a resection procedure with clear surgical margins, leaving no visible tumors behind. In this case report, the clinical presentation, preoperative diagnosis and treatment of a GIST localized in the ileum were reviewed in the light of the literature.